2006
DOI: 10.1021/ma0614545
|View full text |Cite
|
Sign up to set email alerts
|

Solution Properties of Star and Linear Poly(N-isopropylacrylamide)

Abstract: The LCST transitions of novel N-isopropylacrylamide (NIPAM) star polymers, prepared using the four-armed RAFT agent pentaerythritoltetrakis(3-(S-benzyltrithiocarbonyl)propionate) (PTBTP) and their hydrolyzed linear arms were studied using 1 H NMR, PFG-NMR, and DLS. The aim was to determine the effect of polymer architecture and the presence of end groups derived from RAFT agents on the LCST. The LCST transitions of star PNIPAM were significantly depressed by the presence of the hydrophobic star core and possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
158
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(166 citation statements)
references
References 52 publications
5
158
1
2
Order By: Relevance
“…All Tc values were within the same range and independent from molecular weight. This discovery agreed with the observations from Whittaker and coworkers [43]. They reported that the LCST transitions of a four arm star PNIPAAm based on a pentaerythritol moiety were depressed by the presence of the hydrophobic star core.…”
Section: Thermal Phase Transition Behavior Of Star-like Pnipaam Homo supporting
confidence: 91%
“…All Tc values were within the same range and independent from molecular weight. This discovery agreed with the observations from Whittaker and coworkers [43]. They reported that the LCST transitions of a four arm star PNIPAAm based on a pentaerythritol moiety were depressed by the presence of the hydrophobic star core.…”
Section: Thermal Phase Transition Behavior Of Star-like Pnipaam Homo supporting
confidence: 91%
“…For Type II polymers, the architecture has a negligible effect (e.g. the LCST of star PiPAAms is similar to that of linear polymer [109]), except for polymers with hydrophobic or hydrophilic end-groups [110][111][112] and polymers with a high number of arms [113] or spherical brushes [114,115]. Type III polymers [e.g.…”
Section: Phenomenological Classificationmentioning
confidence: 99%
“…[118] Better results in terms of molecular weight distribution were often achieved with other monomers such as PNIPAAm [119,120] and acrylates. [121,122] Reason may be a better segmental diffusion of these polymers.…”
Section: Divergent Star Synthesismentioning
confidence: 99%